{Does Bed Sharing with an Infant Influence Parents' Sexual Life? A Scoping Review in Western Countries} - Vousoura, Eleni; Ekizoglou, Chryssa (Sexes, 2021)
Bed sharing—the sharing of a sleeping surface by parents and children—is a common, yet controversial, practice. While most research has focused on the public health aspect of this practice, much less is known regarding its effect on the marital relationship. The aim of the present study was to conduct a scoping review on the impact of parent–infant bed sharing sleeping practices on the sexual and marital relationship of couples. The qualitative synthesis of six studies on this topic suggests that overall, bed sharing does not exert a significant negative impact on family functioning; when it does, it appears to be related to incongruent parental beliefs and expectations, especially when bed sharing is not an intentional choice of sleep arrangement, and there are other confounding factors such as fatigue and psychological distress. Suggestions for future studies and clinical implications are discussed.